1987
DOI: 10.1002/ajpa.1330720110
|View full text |Cite
|
Sign up to set email alerts
|

Sibling similarity in development of covariation among physical traits in early childhood

Abstract: We studied the sibling similarity in development of covariation among body size characters (body weight (W), body length (S) and head circumference (HC) in Tel Aviv infants from birth up to 2 years of age. We investigated the effects of parental geographic origin, profession, age, current residence, and of family size. Multiple regression analysis with "dummy" procedure established that none of these variables had any significant effect on the aforementioned anthropometric traits. The matrices of phenotypic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The solution to such a complicated problem, which involves simultaneous study of many variables, is possible only within the framework of multivariate analysis. Applications of multivariate analysis to morphometric traits and physical growth of humans and mammalian species are numerous (Relethford et al, 1978;Afifi, 1985;Glassman and Coelho, 1987;Kobyliansky et al, 1987;Arrieta and Lostao, 1988). It is almost universally agreed that physical characteristics of infants, such as body weight, length, and head circumference, on the one hand, and ages of attaining gross motor milestones, on the other hand, are important for the prediction of the child's future developmental status (Hyde, 1986;Illingworth, 1988).…”
mentioning
confidence: 99%
“…The solution to such a complicated problem, which involves simultaneous study of many variables, is possible only within the framework of multivariate analysis. Applications of multivariate analysis to morphometric traits and physical growth of humans and mammalian species are numerous (Relethford et al, 1978;Afifi, 1985;Glassman and Coelho, 1987;Kobyliansky et al, 1987;Arrieta and Lostao, 1988). It is almost universally agreed that physical characteristics of infants, such as body weight, length, and head circumference, on the one hand, and ages of attaining gross motor milestones, on the other hand, are important for the prediction of the child's future developmental status (Hyde, 1986;Illingworth, 1988).…”
mentioning
confidence: 99%
“…Using W C s and VBHs to partition early and later growth through early childhood For reasons described above, studies have repeatedly shown that early and later growth may be independent (see also Hiernaux, 1968). However, it is also becoming possible to distinguish growth through early childhood (age four) by studying anthropometrics (e.g., Kobyliansky et al, 1987).…”
Section: Vertebral Growth and Its Utility For Inferring Gd And Sdmentioning
confidence: 99%